Design and characterization of a hybrid soft gripper with active palm pose control. (December 2020) - Subramaniam, Vignesh; Jain, Snehal; Agarwal, Jai; Valdivia y Alvarado, Pablo
The design and characterization of a soft gripper with an active palm to control grasp postures is presented herein. The gripper structure is a hybrid of soft and stiff components to facilitate integration with traditional arm manipulators. Three fingers and a palm constitute the gripper, all of which are vacuum actuated. Internal wedges are used to tailor the deformation of a soft outer reinforced skin as vacuum collapses the composite structure. A computational finite-element model is proposed to predict finger kinematics. Thanks to its active palm, the gripper is capable of grasping a wide range of part geometries and compliances while achieving a maximum payload of 30 N. The gripper natural softness enables robust open-loop grasping even when components are not properly aligned. Furthermore, the grasp pose of objects with various aspect ratios and compliances can be robustly maintained during manipulation at linear accelerations of up to 15 m/s 2 and angular accelerations of up to 5.23 rad/s 2 .